2016
DOI: 10.11648/j.sjph.20160402.18
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Analysis of Malaria Outbreak in Ankesha District, Awi Zone, Amhara Region, Ethiopia, 2012: Weaknesses in Control Measures and Risk Factors

Abstract: While malaria is mostly an endemic disease in Ethiopia. It may also occur as outbreaks in areas with low seasonal transmission because of an increase in vector breeding sites, migration of infected people into a vector-rich area populated with susceptible individuals, breakdown of vector control measures and resistance of the vectors to insecticides. The aim of this study was to verify, investigate the outbreak epidemiologically and guide intervention measures. We reviewed data from health post records from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
3
1
0
Order By: Relevance
“…The likelihood of occurrence of the outbreak in the current study area increased tenfolds in poorly controlled environment. Similar study finding was also reported from other part of Ethiopia [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The likelihood of occurrence of the outbreak in the current study area increased tenfolds in poorly controlled environment. Similar study finding was also reported from other part of Ethiopia [15].…”
Section: Discussionsupporting
confidence: 92%
“…Age group of 5–14 years and females were more affected with AR of 37 and 29 per 100 population. Studies in India [14], Ethiopia [15] and Zimbabwe [16] showed children and females were more attacked by malaria. The reason may be children have lower immunity and adult women do more activities that exposed them to mosquito breeding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had mosquito breeding site around their houses were more likely to be diseased by malaria than those who didn’t have mosquito breeding site. This is similar with study done in Ankesha, Ameya, Setit Humera, and Asgede Tsimbla districts of Ethiopia [9, 10, 13, 14]. This could be due to the presence of mosquito breeding site that created suitable condition for reproduction of mosquito and infecting more people since most of the populations stayed out door during the night.…”
Section: Discussionsupporting
confidence: 88%
“…Median age of malaria patients were 16 years, which is in line with outbreak investigation done in Ankesha and Asgede Tsimbla districts, Ethiopia [10, 14], but younger than the study done in Guna Yala, Panama where the median age was 25 years [25]. This might be due to majority of the adolescents were spending more time outdoors in this area for agricultural and livestock keeping activities [6].…”
Section: Discussionsupporting
confidence: 71%